MAKLUMAT INDUSTRI DAN SAINS INFORMATION SERVICE FOR COMMERCE & INDUSTRY - Perpustakaan, Hamzah Sendut (Perpustakaan Universiti Sains Malaysia, 2006)
THE NEW SAFE LATEX Vystar Corporation announced that Revertex Malaysia has signed a letter of intent to produce Vytex, the new safe latex. Vytex natural rubber latex represents a dramatic breakthrough in the search for a natural rubber latex in which the antigenic proteins that trigger allergic reactions are deactivated without reducing elasticity. Vytex natural rubber latex is produced through a proprietary process that deactivates antigenic proteins in latex, potentially making it safe for use by most people who are allergenic-protein sensitive, the Atlanta-based company said. According to Vystar President William Doyle, the plan is to scale up to production of Vytex natural rubber latex by next year. This would mean that products made of the revolutionary all-natural rubber latex could be reaching the market in 2007. The implication is that healthcare providers and individuals who have avoided natural rubber latex products due to fear of allergenic reactions will now have a safe choice with all of the favorable characteristic of latex, sources were quoted.